Learning to Like What You Have: Explaining the Endowment Effect - Steffen Huck; Georg Kirchsteiger; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
The endowment effect describes the fact that people demand much more to give up an object than they are willing to spend to acquire it. The existence of this effect has been documented in numerous experiments. We attempt to explain this effect by showing that evolution favors individuals whose preferences embody an endowment effect. The reason is that an endowment effect improves one's bargaining position in bilateral trades. We show that for a general class of evolutionary processes strictly positive endowment effects will survive in the long run.
Keywords: C79; C73; D00; 330; endowment effect; evolution; bargaining; Verhandlungen; Willingness to pay; Evolutionsökonomik; Theorie